PENGARUH KONFIGURASI STRUKTUR TERHADAP KEKUATAN BENDING DARI KOMPOSIT SANDWICH 3D PRINTING - Benny Aprianto Saputra; Ikbal Rizki Putra; Ferry Setiawan (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Sandwich composites are a combination of two materials that have different properties which are then put together to have stronger properties and resistance than their constituents, consisting of the skin and the core. In this study using fiberglass skin, core polylactid acid (PLA) and put together using epoxy resin. One of the new technologies today is 3D printing by working to produce three-dimensional products. In this study, it was used to produce new composite products with variations of honeycomb and rectangular cores combined with 3D printing printed PLA cores. The manufacturing process using the hand lay up method is based on its superiority that the process is simpler. Bending test with the three point bending method is carried out in order to determine the resistance of the specimen to a given bending load. The results obtained after testing where of the three honeycomb cores 1, 2 and 3 obtained the highest bending stress value in honeycomb 2 of 10.732Mpa and a maximum load of 359.573N. Then on the three rectangular cores 1.2 and 3, the highest bending stress value is obtained in rectangular 2 of 10.456Mpa and the maximum load is 252.432N. From the test results it was found that the honeycomb sandwich core composite has superior structural strength compared to the rectangular sandwich core composite.